Vegetable proteins and milk puddings - Sousa, Isabel (2010)
In recent years, interest in animal free foods has increased tremendously due to factors like BSE crisis, rise of nutritionally dependent illnesses, like diabetes type II, cardiovascular and digestive diseases, along with ethic orientations of denying animal intakes of any kind. The use of proteins from leguminous seeds as an alternative to the animal proteins in dairy desserts was studied. Lupin, pea and soya protein isolates were used in combination with k- carrageenan, gellan and xanthan gum, in order to obtain a synergistic effect. Milk puddings were also produced for comparison. Texture studies suggested that mixed protein /polysaccharide systems, with vegetable proteins and k- carrageenan or gellan gum, would be good systems to develop vegetable gelled desserts. Rheological oscillatory measurements were carried out to clarify the kinetics of gelation and characterise the microstructure of the best performing products. Results from time sweep tests showed that formulations with gellan gum present an industrial advantage over formulations with k-carrageenan, since the maturation time for gellan gels is of the order of 5 /10 h compared with 4 /6 days in the case of k-carrageenan. All the mixed gels presented the typical weak gel structure; therefore, it was possible to perform steady-state measurements, which allowed the observation of a shear-thinning behaviour for all gels.